Optimization of Parameters for the Extraction of Phenolic Antioxidants from Boxberry Tree (Myrica esculenta) Bark Using Response Surface Methodology - Do Thi Kieu Trinh, Nguyen Thi Thanh Tinh, Ho Thi Thu Hoa, Nguyen Tien An, Pham Ngoc Tuan, Phan Hoang Dai (King Mongkut’s University of Technology North Bangkok, 2024)
17